Advancements of gene therapy in cancer treatment: a comprehensive review - Mohd Abas, Muhammad Dhiyauddin; Mohd Asri, Muhammad Fareez; Yusafawi, Nur Anis Suffiah; Rosman, Nur Anis Zahra; Baharudin, Nur Arifah Zahidah; Bakhtiar, M Taher; Darnis, Deny Susanti; Khotib, Junaidi (Elsevier, 2024)
Cancer is the main contributor for mortality in the world. Conventional therapy that available as the treatment options are chemotherapy, radiotherapy and surgery. However, these treatments are hardly cell-specific most of the time. Nowadays, extensive research and investigations are made to develop cell-specific approaches prior to cancer treatment. Some of them are photodynamic therapy, hyperthermia, immunotherapy, stem cell trans- plantation and targeted therapy. This review article will be focusing on the development of gene therapy in cancer. The objective of gene therapy is to correct specific mutant genes causing the excessive proliferation of the cell that leads to cancer. There are lots of explorations in the approach to modify the gene. The delivery of this therapy plays a big role in its success. If the inserted gene does not find its way to the target, the therapy is considered a failure. Hence, vectors are needed and the common vectors used are viral, non viral or synthetic, polymer based and lipid based vectors. The advancement of gene therapy in cancer treatment will be focussing on the top three cancer cases in the world which are breast, lung and colon cancer. In breast cancer, the discussed therapy are CRISPR/Cas9, siRNA and gene silencing whereas in colon cancer miRNA and suicide gene therapy and in lung cancer, replacement of tumor suppressor gene, CRISPR/Cas9 and miRNA.